Changes Depression- and Anxiety- like Behaviors following Selective Breeding for Cocaine Reinforcement. (January 2021) - Grasing, Michael J; Xu, Haiyang; Idowu, Jessica Y; Grasing, Kenneth
Highlights: Disorders of mood and anxiety play an important role in substance use Common changes in genotype may underlie both types of behavior In a genetic strain with increased drug-taking, immobility varied with strain and sex Anxiety-like behavior was increased in the line selected for greater cocaine taking This trait may lead to an enhanced motivation for cocaine self-administration Abstract: The LS and HS are rat lines selectively bred for altered cocaine self-administration. Given the importance of mental health in substance use, these lines were evaluated for putative depression- and anxiety- like behaviors through forced swimming and exploration of a plus maze. We found increases of struggling in LS males, climbing in LS females, and swimming in HS males; with biphasic effects on immobility in the HS strain. HS rats had fewer entries into and less time spent in open arms of the plus maze, consistent with greater anxiety-like behavior, which may contribute to enhanced drug taking. Graphical Abstract: Image, graphical abstract